Seismic Design and Risk Analyses of Safe-to-Fail Steel and RC Frames for Nuclear Facilities - Mangkoesoebroto, Sindur P.; Rianto, Shandy (Jurnal Teknik Sipil, 2024)
Abstract In this article, the design and estimate of the collapse risk of safe-to-fail steel and reinforced concrete (RC) frames due to earthquakes were proposed. The frames are part of nuclear facility buildings, and their failures are to follow the safe-to-fail beam side-sway collapse mechanism. The safe-to-fail was dictated by allowing plastic hinges to form merely in beams and few in columns; no other failure but flexure was tolerated such as shear, local or lateraltorsional buckling. Two types of safe-to-fail frames were studied, one with special moment frame (SMF) and the other with ordinary moment frame (OMF). The design was elaborated, and the fragility-based collapse risks were estimated and compared. Nonlinear time history analyses were carried out to evaluate the structural performance. The analyses showed that the safe-to-fail OMF had lower collapse risk than the safe-to-fail SMF for both steel and concrete frames. The steel safe-to-fail OMF showed superior behaviours. Keywords: Safe-to-fail; concrete and steel frames; fragility; collapse risk; earthquake; time history analysis.